Unveiling the Success of Bilebante Tourism Village: Competitiveness, Participation, and Empowerment - Latifah, Annisa Husnul; Hellen; Lawrence, Jennifer (Yayasan Ilomata, 2025)
The Indonesian government positions tourism villages as a strategic instrument for advancing sustainability, yet the determinants of their success remain underexplored. This study investigates how destination competitiveness, community participation, and local empowerment shape the development of Bilebante Village, Lombok. Previous studies have addressed isolated issues such as participation or empowerment, but none have identified the core reasons for the village’s overall success. This gap is critical because identifying what truly makes a village succeed is essential for advancing tourism village development. A qualitative case study was conducted using semi-structured interviews with six purposively selected Pokdarwis members and participatory observation across the village’s zones. Data were analyzed with Miles and Huberman’s interactive model through thematic coding on competitiveness, participation, and empowerment. The findings show that Bilebante’s success emerges from the interaction of three interconnected factors. Its green tourism attractions provide a competitive advantage that is reinforced by strong community participation. Through this participation, residents gain skills and confidence, creating empowerment that drives further innovation and, in turn, strengthens competitiveness. Theoretically, this study contributes to rural tourism literature by showing how competitiveness, participation, and empowerment operate in a mutually reinforcing cycle rather than in isolation. Practically, it highlights that government and external support should integrate these three dimensions, and that initiatives such as community learning hubs and inter-village exchange programs can help replicate Bilebante’s model in other contexts.